Reverberações do arquétipo da fada no romance Jonathan Strange & Mr. Norrell, de Susanna Clarke - Xavier Filho, Haroudo Satiro (2019)
This research aimed to analyze the Fairy archetype in Susanna Clarke's novel Jonathan Strange & Mr Norrell (2016). It is an English book of Fantasy and Alternative History that won and was nominated for the greatest awards of its kind at the time of its publication - 2006. We seek to investigate how the process of adapting the Fairy archetype in the novel took place in the context of the production of the work and the author's choices regarding time, space and previous representations of the archetype. To this end, we built a definition of archetype based on Campbell (1990), Dundes (1996) and Jung (1978), among others. We also used the concept of chronotope (BAKHTIN, 2014), as well as elaborated a typology - limited but sufficient for our purpose - of the Fairy archetype. We used Hutcheon (2006) as the main methodological basis, which consisted in applying the journalistic LIDE (ie the questions: Who? How? Where? How? Why? When?). To the elements of the adaptation of the Fairy archetype in Clarke's novel. According to our analysis, this archetype was represented in two distinct ways in the face of a symbolic clash between forms presented earlier in the history of England: the Fairy as an infernal element and the Fairy as constitutive of the very spirit of England.